Mesoporous CoNC fiber composite platinum-cobalt alloy catalyst and preparation method and application thereof

Through mesoporous CoNC fiber composite platinum-cobalt alloy catalyst, the problems of low utilization rate of platinum-based catalysts and large oxygen transmission resistance in the prior art are solved, and higher fuel cell performance and stability are achieved, through mesoporous structure and order The combination of intermetallic phases avoids nanocrystal agglomeration and shedding, and improves the overall performance of the catalyst.

CN119133487APending Publication Date: 2024-12-13HUAZHONG UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411083775.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The utilization rate of platinum-based catalysts in the existing proton exchange membrane fuel cell cathode catalysts is low and the oxygen transport resistance is large, resulting in poor performance. The traditional ordering treatment leads to agglomeration of platinum-based nanocrystals, reducing the stability of the catalyst.

Method used

The mesoporous CoNC fiber is used to combine platinum-cobalt alloy catalyst to prepare CoNC fibers by electrospinning, etching to form a mesoporous structure, and loading platinum-cobalt alloy nanocrystals, annealing at high temperature to form an ordered intermetallic phase to avoid agglomeration, and use mesoporous The structural domain-limiting effect prevents nanocrystals from falling off.

Benefits of technology

It improves the mass transfer performance and stability of the catalyst, reduces the risk of toxicity of platinum, optimizes the electronic structure of platinum-cobalt nanocrystals, enhances the catalytic activity of the active site, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133487A_ABST
    Figure CN119133487A_ABST
Patent Text Reader

Abstract

The invention belongs to the related technical field of proton exchange membrane fuel cells, and discloses a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst and a preparation method and application thereof.The method comprises the following steps that 1, organic polymers, Co-doped ZIF8, an oxide pore-forming agent and N, N-dimethylformamide are mixed and dispersed evenly to obtain an electrostatic spinning solution, and the electrostatic spinning solution is subjected to electrostatic spinning; a CoNC fiber precursor is prepared through an electrostatic spinning machine, and then the obtained CoNC fiber precursor is carbonized to obtain CoNC fibers; (2) etching the obtained CoNC fiber with an etching solution to obtain a mesoporous CoNC fiber; and (3) dispersing the obtained mesoporous CoNC fibers in a solvent, and loading platinum-cobalt alloy nanocrystals, thereby obtaining the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst. According to the invention, the oxygen transmission resistance of the fuel cell under high current density can be reduced, and the platinum-based nanocrystals in the catalyst are loaded in the mesopores of the carbon carrier, so that the poisoning of ionomers can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to proton exchange membrane fuel cells, and more specifically, relates to a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen energy has received widespread attention as a green and pollution-free form of energy, and proton exchange membrane fuel cells, as an important application method in the field of hydrogen energy, have also received attention from scientific research institutions at home and abroad.

[0003] However, proton exchange membrane fuel cells have not yet been applied on a large scale. The main limiting factor is that their cathode requires a large amount of platinum as a catalyst, but platinum is expensive and has limited reserves. Studies have found that alloying transition metals with platinum can effectively improve the activity of platinum-based catalysts and reduce the amount of platinum used in fuel cells. At the same time, by ordering the platinum-based alloy, its activity and stability can be further improved. However, high-temperature annealing is required during the ordering process, which will cause the platinum-based nanocrystal particles to become larger and reduce the utilization rate of platinum.

[0004] Studies have found that the carrier in the cathode catalyst of fuel cells also has a significant impact on the performance of fuel cells. The pore structure of the fuel cell catalyst carrier has an important influence on the utilization rate of the platinum-based catalyst under operating conditions and the mass transfer of the catalyst layer. However, the research on the design and preparation methods of fuel cell carriers is still in its infancy. In order to further improve the performance of fuel cell catalysts and realize large-scale commercial use, the research on the design and preparation methods of new carriers is particularly urgent. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst and a preparation method and application thereof, which aims to solve the problems that the existing catalyst Pt is easily poisoned by ionomers, resulting in low Pt utilization and large oxygen transmission resistance resulting in poor performance.

[0006] To achieve the above object, according to one aspect of the present invention, a method for preparing a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst is provided, the method comprising the following steps:

[0007] (1) mixing and dispersing an organic polymer, Co-doped ZIF8, an oxide pore former, and N,N-dimethylformamide to obtain an electrospinning solution, and then preparing a CoNC fiber precursor by an electrospinning machine, and then carbonizing the obtained CoNC fiber precursor to obtain CoNC fibers;

[0008] (2) etching the obtained CoNC fiber using an etching solution to obtain a mesoporous CoNC fiber;

[0009] (3) The obtained mesoporous CoNC fibers are dispersed in a solvent and loaded with platinum-cobalt alloy nanocrystals to obtain a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst.

[0010] Furthermore, after the platinum-cobalt alloy nanocrystals are loaded, high-temperature annealing is performed in an argon-hydrogen mixed gas to obtain a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst.

[0011] Furthermore, the oxide pore former is one or a mixture of nano gas-phase hydrophilic silica, nano magnesium oxide, and nano calcium oxide.

[0012] Furthermore, the preparation steps of Co-doped ZIF8 are as follows: first, dimethylimidazole and a pore-forming agent are ultrasonically dispersed in a methanol solution to obtain a solution A, cobalt nitrate hexahydrate and zinc nitrate hexahydrate are dissolved in a methanol solution to obtain a solution B, and then the solution B is added dropwise to the solution A, and Co-doped ZIF8 is obtained after reaction at room temperature.

[0013] Furthermore, the mesoporous CoNC fibers are loaded with platinum-cobalt alloy nanocrystals by an ethylene glycol method, an impregnation method or an oleylamine method.

[0014] Furthermore, the atomic structure of the platinum-cobalt alloy nanocrystal is an L10 ordered structure, and the atomic ratio of platinum:cobalt is 1:1.

[0015] Furthermore, the particle size of the platinum-cobalt alloy nanocrystals is 4nm-6nm, and the loading amount is 20wt%-40wt%.

[0016] The present invention also provides a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst, which is prepared by the preparation method of the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst as described above, and comprises mesoporous CoNC fibers and platinum-cobalt alloy nanocrystals, wherein the mesoporous CoNC fibers serve as carriers; the platinum-cobalt alloy nanocrystals are ordered intermetallic phase structure nanocrystals, which are loaded in the mesopores of the mesoporous CoNC fibers.

[0017] Furthermore, the catalyst is a one-dimensional linear structure m; the pore size of the mesoporous CoNC fiber is 4nm to 10nm, and the pore volume is (0.27cm 3 / g~0.88cm 3 / g].

[0018] The present invention also provides a use of the above-mentioned mesoporous CoNC fiber composite platinum-cobalt alloy catalyst in a cathode catalyst layer of a proton exchange membrane fuel cell.

[0019] In general, compared with the prior art, the above technical solutions conceived by the present invention mainly have the following beneficial effects:

[0020] 1. The present invention introduces oxides as templates (pore formers) during the preparation process. Such pore formers do not react at high temperatures and are therefore called hard templates. They can be removed by subsequent treatment to play a pore-forming role. The mesoporous carbon material prepared by the hard template method is relatively stable even when the carbonized hard template is carbonized at high temperatures and will not react, shrink or other adverse phenomena occur, so it will not affect the subsequent pore formation. The pore size of the prepared mesoporous carbon carrier is 4nm to 10nm, and the pore volume can reach 0.88cm 3 / g, so that the prepared carbon carrier has a high degree of graphitization while retaining a rich pore structure. The carbon carrier with rich mesopores and a high degree of graphitization will have better mass transfer performance and stability when used in fuel cells.

[0021] 2. The one-dimensional carbon fiber-like carbon material prepared by electrospinning is a one-dimensional fiber structure formed by continuous carbon atoms. Compared with spherical carbon, this type of structure can conduct electrons through continuous carbon atoms and has better electronic conductivity. The catalyst prepared by the present invention is applied to the cathode of a fuel cell to form a catalytic layer with a mesh structure, so that the catalyst layer has a richer pore structure and a macroporous structure (300nm to 400nm), which is beneficial to the transmission of oxygen and the discharge of water, thereby improving the mass transfer performance of the fuel cell.

[0022] 3. The catalyst realizes phase transformation through high temperature annealing to form an ordered intermetallic phase. The traditional preparation method easily leads to agglomeration of nanocrystals in this process; however, the present invention adopts a preparation method based on a mesoporous carbon carrier. The platinum-cobalt alloy nanocrystals are located in the mesopores and are affected by a certain confinement effect. Agglomeration can be effectively avoided at high temperatures. Therefore, the present invention can prepare platinum-cobalt ordered intermetallic phase nanocrystals with smaller particle size.

[0023] 4. Platinum-cobalt alloy nanocrystals are placed in mesopores, which can prevent the ionomer from directly contacting the surface of the platinum-cobalt nanocrystals to avoid poisoning. At the same time, the confinement effect of the mesoporous structure can ensure that the platinum-cobalt nanocrystals are not easy to agglomerate under the working conditions of the fuel cell, thereby improving the stability of the catalyst.

[0024] 5. The interaction between Pt-Co nanocrystals and CoNC in the carrier can optimize the electronic structure of Pt-Co nanocrystals, making them have better adsorption energy for oxygen-containing intermediates. This interaction can also strengthen the anchoring of Pt-Co nanocrystals in the carrier, avoiding the agglomeration and shedding of nanocrystals under fuel cell conditions, which may lead to decreased activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of the mesoporous CoNC fiber prepared in Example 1 of the present invention;

[0026] Figure 2 is a pore size distribution diagram of the mesoporous CoNC before and after silicon dioxide etching in Example 1 of the present invention;

[0027] Figure 3 is a pore size distribution diagram of the mesoporous CoNC before and after silicon dioxide etching in Example 1 of the present invention;

[0028] Figure 4 is an X-ray diffraction pattern of the L10-PtCo / M-CoNC-NFs catalyst prepared in Example 1 of the present invention;

[0029] Figure 5 This is a transmission electron microscope test image of the L10-PtCo / M-CoNC-NFs catalyst prepared in Example 1 of the present invention;

[0030] Figure 6 This is a test diagram of oxygen reduction activity and stability of the L10-PtCo / M-CoNC-NFs catalyst prepared in Example 1 of the present invention;

[0031] Figure 7 This is a performance test diagram of a single cell of a L10-PtCo / M-CoNC-NFs catalyst fuel cell prepared in Example 1 of the present invention;

[0032] Figure 8 is an X-ray diffraction pattern of the L10-PtCo / M-CoNC-NFs catalyst prepared in Example 2 of the present invention;

[0033] Fig. 9 This is a transmission electron microscope test image of the L10-PtCo / M-CoNC-NFs catalyst prepared in Example 2 of the present invention;

[0034] Fig.10 This is a test diagram of oxygen reduction activity and stability of the L10-PtCo / M-CoNC-NFs catalyst prepared in Example 2 of the present invention;

[0035] Fig.11 This is a performance test diagram of a single cell of the L10-PtCo / M-CoNC-NFs catalyst fuel cell prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0037] The catalyst carrier of proton exchange membrane fuel cell has an important influence on the performance of fuel cells. The distribution of pore structure in the catalyst carrier has a certain influence on the material transport and dispersion of ionomers in fuel cells. The appropriate pore size and pore volume (the suitable pore size of mesoporous carbon materials in fuel cell applications is 4nm~10nm, and the pore volume of 4~10nm mesopores is >0.27cm 3 / g; The pore size of the carrier of the present invention can reach 4nm~10nm, and the pore volume of 4~10nm mesopores is (0.27cm 3 / g~0.88cm 3 / g]), which can reduce the oxygen transmission resistance of the fuel cell under high current density, and the platinum-based nanocrystals in the catalyst are loaded in the mesopores of the carbon carrier, which can avoid the poisoning of the ionomer. At the same time, the interaction between the catalyst carrier and the platinum-based nanocrystals can not only change the electronic structure of the active site, further increase the catalytic activity of the active site, but also the strong interaction between the carrier and the platinum-based nanocrystals can also improve the stability of the platinum-based nanocrystals under fuel cell working conditions, and can slow down the problems of activity decline caused by the agglomeration and migration of the platinum-based nanocrystals. At the same time, ordered platinum-cobalt alloy nanocrystals, due to their unique atomic structure, have better catalytic activity for oxygen reduction than pure platinum nanocrystals and disordered platinum-cobalt nanocrystals. However, the preparation of ordered platinum-cobalt nanocrystals currently requires high-temperature annealing, resulting in a larger particle size of the obtained ordered platinum-cobalt nanocrystals. Therefore, the present invention introduces a cobalt-nitrogen-carbon carrier rich in a mesoporous structure during the preparation process, and uses a loading method such as an ethylene glycol method, an impregnation method, or an oleylamine method to load the platinum nanocrystals. The platinum nanocrystals will be evenly distributed in the mesoporous carrier. In the subsequent high-temperature phase transition reaction, the platinum nanocrystals are confined by the pores. In the process of forming an ordered alloy with the excess cobalt in the carrier, the agglomeration and growth of the platinum-cobalt nanocrystals can be effectively avoided, thereby effectively reducing the particle size of the ordered platinum-cobalt nanocrystals.

[0038] The present invention provides a method for preparing a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst, and the preparation method mainly comprises the following steps:

[0039] (1) An organic polymer, Co-doped ZIF8, a pore-forming agent, and N,N-dimethylformamide are uniformly dispersed to obtain an electrospinning solution, and then a CoNC fiber precursor is prepared by an electrospinning machine, and then the obtained CoNC fiber precursor is carbonized to obtain CoNC fibers.

[0040] The preparation steps of Co-doped ZIF8 are as follows: first, dimethylimidazole and a pore-forming agent are ultrasonically dispersed in a methanol solution to obtain a solution A, cobalt nitrate hexahydrate and zinc nitrate hexahydrate are dissolved in a methanol solution to obtain a solution B, and then the solution B is added dropwise to the solution A, and reacted at room temperature for a certain time to obtain Co-doped ZIF8; wherein the pore-forming agent is an oxide pore-forming agent.

[0041] The molar ratio of dimethylimidazole: zinc nitrate hexahydrate: cobalt nitrate hexahydrate is 50:(5-10):(1-5), the molar ratio of dimethylimidazole: methanol is 1:(2000-5000), the molar ratio of zinc nitrate and cobalt nitrate: methanol is 1:(2000-5000), the corresponding pore-forming agent is one or a mixture of nano gas-phase hydrophilic silica, nano magnesium oxide, and nano calcium oxide, the particle size of the pore-forming agent is 5nm-50nm, the ultrasonic dispersion time is 2h-10h, and the reaction time at room temperature is 12h-24h.

[0042] In this embodiment, the organic polymer is one or a mixture of polyvinyl pyrrolidone, polyacrylonitrile, and polyaniline, and the mass ratio of organic polymer: Co-doped ZIF8: pore-forming agent is 4:(3-5):(1-2). The electrospinning solution is dispersed in ultrasound for 5h-12h and stirred for 12h-24h. The positive voltage of the electrospinning is 10kV-15kV, the negative voltage is -1kV--2kV, the injection speed is 0.4mm / min-0.6mm / min, the carbonization temperature is 900℃-1200℃, the carbonization time is 1h-5h, and the heating rate is 1℃ / min-10℃ / min.

[0043] (2) The obtained CoNC fibers are etched with an etching solution to obtain mesoporous CoNC fibers.

[0044] The concentration of the etching solution used is 2M to 4M, the etching time is 12h to 24h, and the etching temperature is 70° C. to 90° C. The etching solution can be a sodium hydroxide solution or a sulfuric acid solution.

[0045] (3) The obtained mesoporous CoNC fibers are dispersed in a solvent, and platinum-cobalt alloy nanocrystals are loaded by an ethylene glycol method, and then high-temperature annealing is performed in an argon-hydrogen mixed gas to obtain a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst.

[0046] The solvent for dispersing mesoporous CoNC is a mixture of ethylene glycol and isopropanol, with a volume ratio of 10:(1-5), the ultrasonic dispersion time is 2h-6h, the temperature of loading platinum nanocrystals by ethylene glycol method is 130°C-180°C, the reaction time is 2h-6h, the precursor of the platinum nanocrystals is one or more of chloroplatinic acid, platinum nitrate, and platinum acetylacetonate, the mixed gas of argon and hydrogen is 5%-10% hydrogen / argon, the annealing temperature is 600°C-900°C, the heating rate is 1°C / min-10°C / min, and the annealing time is 2h-5h.

[0047] The present invention also provides a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst prepared by the above method, which can improve the cathode oxygen reduction activity and stability of proton exchange membrane fuel cells. The catalyst comprises mesoporous CoNC fibers and platinum-cobalt alloy nanocrystals, wherein the mesoporous CoNC fibers serve as carriers; the platinum-cobalt alloy nanocrystals are ordered intermetallic phase structure nanocrystals, which are loaded in the mesopores of the mesoporous CoNC fibers.

[0048] The catalyst has a one-dimensional linear structure, and the abundant mesopores can effectively improve the mass transfer performance under fuel cell operating conditions, reduce platinum poisoning, and improve platinum utilization. In addition, the introduction of CoNC structure into the carrier can produce a synergistic effect with the loaded platinum-cobalt intermetallic phase nanocrystals, further improving the intrinsic activity and stability of the catalyst.

[0049] The mesoporous CoNC fiber composite platinum-cobalt alloy catalyst has a mesopore size of 3nm to 20nm, and a CoNC fiber diameter of 200nm to 500nm. The particle size of the platinum-cobalt alloy nanocrystal is 4nm to 6nm, and is loaded in the mesopores of the mesoporous CoNC carrier, with a loading amount of 20wt% to 40wt%. The atomic structure of the platinum-cobalt alloy nanocrystal is an L10 ordered structure, and the atomic ratio of platinum to cobalt is 1:1.

[0050] In another embodiment, the above-mentioned ethylene glycol method can be replaced by an impregnation method and oleylamine as a solvent method, wherein the steps of loading platinum nanocrystals by the impregnation method are: first, the Pt precursor is dispersed in a volatile solvent such as ethanol / acetone / isopropanol, and then a certain amount of carbon carrier is added, and ultrasonic dispersion is performed for 0.5h to 2h, and then it is stirred and dried under stirring and heating (60°C to 80°C), and then annealed at 300°C in an Ar / H2 atmosphere for 1h.

[0051] The specific steps of the oleylamine method are as follows: a certain amount of Pt precursor is dispersed in an oleylamine solution, added into a four-necked flask, then Ar gas is introduced for 30 minutes, the temperature is raised to 100°C, BTB (borane-tert-butylamine complex) is added, the reaction is performed for 0.5 hours, then centrifuged and washed, dispersed in n-hexane, and finally mixed and dispersed on a carbon carrier, and then centrifuged and dried to obtain the product.

[0052] The present invention also provides a use of the above-mentioned mesoporous CoNC fiber composite platinum-cobalt alloy catalyst in a cathode catalyst layer of a proton exchange membrane fuel cell.

[0053] The present invention is further described in detail below with reference to specific embodiments.

[0054] Example 1

[0055] The preparation method of the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst provided in Example 1 of the present invention is as follows:

[0056] (1) First, 4.6 g of dimethylimidazole, 200 mg of fumed silica (particle size of about 7 nm), and 100 ml of methanol were weighed into a 500 ml beaker and ultrasonically dispersed for 30 min to obtain liquid A. Then, 0.37 g of cobalt nitrate hexahydrate, 3.3 g of zinc nitrate hexahydrate, and 100 ml of methanol were weighed into a 500 ml beaker and ultrasonically dispersed for 30 min to obtain liquid B. Finally, liquid B was added to liquid A under stirring, reacted at room temperature for 12 h, centrifuged and washed 3 times, and vacuum dried to obtain SiO2 composite Co-doped ZIF8 nanoparticles (SiO2 / Co-ZIF8).

[0057] (2) First, 0.4 g of polyacrylonitrile (PAN, molecular weight 150,000), 0.1 g of polyvinyl pyrrolidone (PVP, molecular weight 8000), 50 mg of fumed silica (particle size about 7 nm), 0.45 g of SiO2 / Co-ZIF8 nanoparticles prepared in step (1), and 6 ml of N,N-dimethylformamide were weighed in a 30 ml glass bottle, stirred at 60 ° C for 12 h, and ground for 30 min to obtain a composite electrospinning solution. Then, PAN / PVP / Co-ZIF8 / SiO2 composite fibers were spun under the conditions of positive voltage 11 kV, negative voltage -1.0 kV, and extrusion speed 0.6 ml / min.

[0058] (3) The PAN / PVP / Co-ZIF8 / SiO2 composite fiber obtained in step (2) was pretreated at 230°C in an air atmosphere for 1 h, then carbonized at 950°C for 2 h in a N2 atmosphere, and then washed in a 4M NaOH solution at 90°C for 24 h to remove SiO2 and obtain a porous CoNC fiber carrier.

[0059] (4) Weigh 30 mg of the porous CoNC fiber obtained in step (3) and 20 ml of isopropanol into a 50 ml beaker and ultrasonically disperse for 30 min. Then, the mesoporous CoNC dispersion was added dropwise to a 100 ml four-necked flask containing 20 ml of ethylene glycol and 20 mg of hexahydrated chloroplatinic acid under stirring, heated to 150°C, reacted for 2 h, centrifuged, washed and dried to obtain a platinum nanocrystalline composite porous CoNC fiber catalyst. The dried sample was annealed at 800°C for 1 h in a 5% H2 / Ar / mixed atmosphere to obtain an ordered platinum cobalt nanocrystalline composite mesoporous CoNC fiber catalyst (L10-PtCo / M-CoNC-NFs).

[0060] The PAN / PVP / Co-ZIF8 / SiO2 composite fiber prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the spinning diameter is about 300-400nm, and the Co-ZIF8 particles are evenly dispersed on the fiber surface; and after carbonization, its fiber structure is maintained, but it is obvious that there are many pore structures on the fiber surface ( Figure 2 As shown in the figure, after removing SiO2 by alkali washing, a mesoporous structure with a pore size ranging from 8nm to 30nm was introduced, and the pore volume was significantly improved ( Figure 3 As shown). In summary, this example successfully prepared a mesoporous CoNC fiber carbon carrier, loaded with 20% platinum nanocrystals by the ethylene glycol method, and obtained an L10 type ordered platinum-cobalt nanocrystal composite mesoporous CoNC fiber catalyst with a particle size of only about 3nm to 4nm after high temperature annealing (as shown Figure 4 , Figure 5 The catalyst showed excellent activity and stability in the half-cell test (as shown in Figure 6 As shown). The half-wave potential is 0.945V, and the half-wave potential decays by 3mV in the 30,000-cycle cycle stability test; and the catalyst is applied to proton exchange membrane fuel cells, showing excellent activity and stability in the mass transfer area, indicating that the composite catalyst has excellent mass transfer performance (such as Figure 7 shown).

[0061] Example 2

[0062] The preparation method of the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst provided in Example 2 of the present invention is as follows:

[0063] (1) First, 3.2 g of dimethylimidazole, 200 mg of magnesium oxide (MgO) with a particle size of 20 nm, and 200 ml of methanol were weighed into a 500 ml beaker and ultrasonically dispersed for 30 min to obtain liquid A. Then, 3.2 g of cobalt nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 200 ml of methanol were weighed into a 500 ml beaker and ultrasonically dispersed for 30 min to obtain liquid B. Finally, liquid B was added to liquid A under stirring, reacted at room temperature for 12 h, centrifuged and washed 3 times, and vacuum dried to obtain MgO composite Co-doped ZIF8 nanoparticles (MgO / Co-ZIF8).

[0064] (2) First, weigh 0.5 g of polyaniline (PAn, molecular weight 100,000), 0.1 g of polyvinyl pyrrolidone (PVP, molecular weight 8000), 150 mg of MgO (particle size about 20 nm), 0.5 g of MgO / Co-ZIF8 nanoparticles prepared in step (1), and 7 ml of N,N-dimethylformamide in a 30 ml glass bottle, stir at 60 ° C for 12 h, and grind for 30 min to obtain a composite electrospinning solution; then, spin at a positive voltage of 14 kV, a negative voltage of -2.0 kV, and an extrusion speed of 0.6 ml / min to obtain PAn / PVP / Co-ZIF8 / MgO composite fibers.

[0065] (3) The PAn / PVP / Co-ZIF8 / MgO composite fiber obtained in step (2) was pretreated at 230°C in an air atmosphere for 1 h, then carbonized at 1000°C for 2 h in a N2 atmosphere, and then washed in a 2M sulfuric acid solution at 60°C for 12 h to remove MgO and obtain a mesoporous CoNC fiber carrier.

[0066] (4) Weigh 30 mg of the porous CoNC fiber obtained in step (3) and 20 ml of isopropanol into a 50 ml beaker and ultrasonically disperse for 30 min; then drop the mesoporous CoNC dispersion into a 100 ml four-necked flask containing 20 ml of ethylene glycol and 33 mg of platinum nitrate under stirring, heat to 150° C., react for 3 h, centrifuge, wash and dry to obtain a platinum nanocrystalline composite mesoporous CoNC fiber catalyst. The dried sample is annealed at 900° C. for 1 h in a 5% H2 / Ar / mixed atmosphere to obtain an ordered platinum cobalt nanocrystalline composite mesoporous CoNC fiber catalyst (L10-PtCo / M-CoNC-NFs).

[0067] Depend on Figure 8 and Fig. 9 Analysis shows that in this embodiment, ordered platinum-cobalt nanocrystals with a particle size of about 3nm to 4nm were prepared and loaded on the porous CoNC fibers. Fig.10Analysis shows that the catalyst prepared in Example 2 has excellent half-cell activity and stability, with only a 5mV decay after 30,000 cycles. Fig.11 Analysis shows that the porous carbon CoNC fiber composite ordered platinum cobalt nanocrystalline catalyst in this embodiment has a higher current density in the mass transfer zone in the proton exchange membrane fuel cell (PEMFC), indicating that the composite catalyst has excellent mass transfer performance.

[0068] The performance test results of Examples 1-2 of the present invention and the commercial control samples are shown in Table 1.

[0069] Table 1, 0.67V current density and peak power density test results

[0070] Test samples 0.67V current density Peak power density Commercial control sample <![CDATA[1070mA / cm 2 ]]> <![CDATA[990mW / cm 2 ]]> Example 2 <![CDATA[1217mA / cm 2 ]]> <![CDATA[1074mW / cm 2 ]]> Example 1 <![CDATA[1306mA / cm 2 ]]> <![CDATA[1166mW / cm 2 ]]>

[0071] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst, characterized in that: The method comprises the following steps: (1) mixing and dispersing an organic polymer, Co-doped ZIF8, an oxide pore former, and N,N-dimethylformamide to obtain an electrospinning solution, thereby preparing a CoNC fiber precursor, and then carbonizing the obtained CoNC fiber precursor to obtain CoNC fibers; (2) etching the obtained CoNC fiber using an etching solution to obtain a mesoporous CoNC fiber; (3) The obtained mesoporous CoNC fibers are dispersed in a solvent and loaded with platinum-cobalt alloy nanocrystals to obtain a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst.

2. The method for preparing the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to claim 1, characterized in that: After loading platinum-cobalt alloy nanocrystals, high-temperature annealing is performed in an argon-hydrogen mixed gas to obtain a mesoporous CoNC fiber composite platinum-cobalt alloy catalyst.

3. The method for preparing the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to claim 1, characterized in that: The oxide pore-forming agent is one or a mixture of nano gas-phase hydrophilic silicon dioxide, nano magnesium oxide, and nano calcium oxide.

4. The method for preparing the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to claim 1, characterized in that: The preparation steps of Co-doped ZIF8 are as follows: first, dimethylimidazole and a pore-forming agent are ultrasonically dispersed in a methanol solution to obtain a solution A, cobalt nitrate hexahydrate and zinc nitrate hexahydrate are dissolved in a methanol solution to obtain a solution B, and then the solution B is added dropwise to the solution A, and Co-doped ZIF8 is obtained after reaction at room temperature.

5. The method for preparing the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to any one of claims 1 to 4, characterized in that: Mesoporous CoNC fibers are loaded with platinum-cobalt alloy nanocrystals by ethylene glycol method, impregnation method or oleylamine method.

6. The method for preparing the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to any one of claims 1 to 4, characterized in that: The atomic structure of the platinum-cobalt alloy nanocrystal is an L10 ordered structure, and the atomic ratio of platinum:cobalt is 1:

1.

7. The method for preparing the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to claim 6, characterized in that: The particle size of the platinum-cobalt alloy nanocrystal is 4 nm to 6 nm, and the loading amount is 20 wt % to 40 wt %.

8. A mesoporous CoNC fiber composite platinum-cobalt alloy catalyst, characterized in that: The catalyst is prepared by the preparation method of the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to any one of claims 1 to 7, and comprises mesoporous CoNC fibers and platinum-cobalt alloy nanocrystals; the platinum-cobalt alloy nanocrystals are ordered intermetallic phase structure nanocrystals, which are loaded in the mesopores of the mesoporous CoNC fibers.

9. The mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to claim 8, characterized in that: The catalyst is a one-dimensional linear structure; the pore size of the mesoporous CoNC fiber is 4nm to 10nm, and the pore volume is (0.27cm 3 / g~0.88cm 3 / g].

10. Use of the mesoporous CoNC fiber composite platinum-cobalt alloy catalyst according to claim 8 or 9 in a cathode catalyst layer of a proton exchange membrane fuel cell.